Development of the active ageing awareness questionnaire in Malaysia - Ahmad Bahuri, Nor Hana (MDPI, 2021)
The world's ageing population is associated with increased morbidity, disability, and social and financial insecurity, which may affect quality of life (QoL). Therefore, the World Health Organization (WHO) endorsed the Active Ageing Framework (AAF) in 2002 to enhance QoL as people age. However, little is known about the status of awareness of active ageing among the population, and there is no appropriate tool for assessment. Hence, the Awareness of Active Ageing Questionnaire (AAAQ) was developed. The content, linguistic and face validations together with test-retest reliability were conducted. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed to test the structural validity of the AAAQ. A total of 110 participants (mean +/- SD = 50.19 +/- 5.52) were selected for the pilot, 81 participants (mean +/- SD = 49.40 +/- 5.70) for the test-retest, and 404 participants (mean +/- SD = 49.90 +/- 5.80) for CFA and EFA tests. The 16-item AAAQ Malay version showed satisfactory reliability and validity. The Cronbach's alpha was more than 0.7 and showed good fit: Cmin/df = 2.771, GFI = 0.903, TLI = 0.951, RMSEA = 0.08. The AAAQ is suitable for measuring the awareness of active ageing among the middle-aged population in Malaysia.